Review of Insurance Law in the Perspective of Sharia Insurance: An Analysis of Principles and Implementation in Indonesia - David Nwanna Dumbiri; Jumriati Hasibuan; Nurul Fadhilah Pasaribu; Hafnina Zahra; Siti Khirani Azzahra (Jurnal Cendikia ISNU SU, 2025)
Insurance is an important part of the modern economic system that plays a role in providing protection against unforeseen financial risks. In the context of sharia economics, conventional insurance is often seen as incompatible with sharia principles because it contains elements of riba, gharar (uncertainty), and maysir (speculation). As an alternative, the concept of sharia insurance (takaful) emerged which is based on the principle of helping and protecting each other between participants. This research aims to examine insurance from the perspective of Islamic law and highlight how sharia principles are applied in the practice of sharia insurance in Indonesia. Using a descriptive qualitative approach and literature study as the main method, this study found that sharia insurance has a strong legal foundation both in terms of fiqh and laws and regulations in Indonesia. The results of this study are expected to provide a deeper understanding for the Muslim community regarding the halalness of insurance products and encourage the development of a sustainable Islamic financial system.